2018
DOI: 10.1016/j.ejso.2018.01.098
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to best practice consensus guidelines for implant-based breast reconstruction: Results from the iBRA national practice questionnaire survey

Abstract: IntroductionThe 2008 National Mastectomy and Breast Reconstruction Audit demonstrated marked variation in the practice and outcomes of breast reconstruction in the UK. To standardise practice and improve outcomes for patients, the British professional associations developed best-practice guidelines with specific guidance for newer mesh-assisted implant-based techniques. We explored the degree of uptake of best-practice guidelines within units performing implant-based reconstruction (IBBR) as the first phase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Most studies (n = 36, 87.8%) assessed adherence based on medical records (from hospital databases, specific registers, or national cancer registries), and their sample sizes ranged from 131 [51] to 104,201 records [44]. The remaining five studies (12.2%) were based on self-reported data, through surveys or interviews to healthcare providers [52][53][54][55][56], and their samples sizes ranged from 10 [56] to 202 participants [53]. Adherence to CGs recommendations was the primary outcome in 38 studies (92.6%), while three focused on factors that influence adherence [32,47,56].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies (n = 36, 87.8%) assessed adherence based on medical records (from hospital databases, specific registers, or national cancer registries), and their sample sizes ranged from 131 [51] to 104,201 records [44]. The remaining five studies (12.2%) were based on self-reported data, through surveys or interviews to healthcare providers [52][53][54][55][56], and their samples sizes ranged from 10 [56] to 202 participants [53]. Adherence to CGs recommendations was the primary outcome in 38 studies (92.6%), while three focused on factors that influence adherence [32,47,56].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These studies included patients receiving treatment in the period from 1992 to 2008 [20,35,63].The median adherence for surgical procedures was 86.3% (IQR 75.7-89.2%), and ranged from 65 [63] to 92% [35]. Moreover, eleven studies measured adherence for individual surgical procedures which included (1) breast-conserving surgery (BCS) [45,58,[60][61][62], the median adherence was 74% (IQR 75.7-93%), and ranged from 35 [60] to 95% [45]; (2) mastectomy (MA) [25,45,60], the adherence ranged from 54 [60] to 91% [45]; (3) SLNB [58,62,72], from 51 [62] to 76% [72]; (4) ALND [58,59,73], from 68 [58] to 81% [59]; and (5) other indicators included organisational indicators [54] or "breast surgery without needing a second surgery" [57], which reported 17% and 97% of adherent treatment, respectively.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This work comprises phase 3, the Randomisation Acceptability Phase of the iBRA study (ISRCTN37664281) a multicentre prospective cohort study to inform the feasibility, design and conduct of a large-scale pragmatic RCT in IBBR. The study protocol [25] and results of phases 1 [26,27] and 2 [9] have been published elsewhere. Full ethical approval for phase 3 was obtained from the University of Bristol Faculty of Health Sciences Research Ethics Committee (FREC) Reference 61,501.…”
Section: Methodsmentioning
confidence: 99%
“…Phase 1 was a national practice questionnaire aiming to survey current practice, with phase 2 involving a multicentre prospective cohort study of patients undergoing IBBR to evaluate the clinical and patient-reported outcomes of these procedures. Phase 3 of the study used mixed-methods to investigate the acceptability of candidate trial designs generated in phase 1 [26,27] and phase 2 [9]. This included an electronic survey and qualitative interviews, which aimed to explore the acceptability of proposed RCT designs and possible barriers to RCT conduct in IBBR, from the perspective of those who would be potential trial recruiters.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%